Pengaruh enjoyment dan persepsi kegunaan terhadap continuance intention pada layanan over the top lokal - Puspasari, Suci Indah; Rojuaniah, Rojuaniah (Implementasi Manajemen & Kewirausahaan, 2023)
The increasing knowledge of the public about digital TV, the government in 2022 decide analog TV migrates to digital or can be called analog switch off (ASO). The purpose of this study is to analyze enjoyment, perceived usefulness, customer satisfaction, and continuance intention. In this study use a quantitative approach aimed at testing the predetermined hypothesis. The population used is vidio.com’s app users in the Bekasi region, and the total sample in this study is 120 samples. Data analysis in this study used Structural Equation Modelling Partial Least Square (SEM-PLS). The results from the study found that the higher the influence of enjoyment and perceived usefulness, the higher the level of customer satisfaction. The increase in customer satisfaction, the higher the influence of continuance intention. Enjoyment and perceived usefulness does not affect continuance intention. Customer satisfaction mediates the relationship between enjoyment and continuance intention. Customer satisfaction can mediate the effect of enjoyment on continuance intention and the effect of perceived usefulness on continuance intention.